Artistas, artesanos, liberalismo y sociabilidades republicanas en Ecuador, 1845-1859 (Dossier: Historias críticas del arte; diálogos transdisciplinarios e indagaciones sobre la estructuración del campo artístico) - Borja González, Grethy Galaxis (2018)
The article examines the republican sociability that was cultivated in associations and forums that were established to provide vocational and artistic training to craftsmen and artists in Ecuador from 1845 to 1859. In order to discuss the close ties between politics and culture, it addresses four interconnected themes: the relationship between associations of craftsmen and the liberal governments arising from the March 1845 Revolution; associations viewed as forums for learning and the exercise of political rights by craftsmen; the standards governing the functioning of these entities; and ultimately the thoughts that artists and craftsmen wrote down while building the republican order.